2018
DOI: 10.1021/acsami.8b08562
|View full text |Cite
|
Sign up to set email alerts
|

Welcoming Gallium- and Indium-Fumarate MOFs to the Family: Synthesis, Comprehensive Characterization, Observation of Porous Hydrophobicity, and CO2 Dynamics

Abstract: The properties and applications of metal-organic frameworks (MOFs) are strongly dependent on the nature of the metals and linkers, along with the specific conditions employed during synthesis. Al-fumarate, trademarked as Basolite A520, is a porous MOF that incorporates aluminum centers along with fumarate linkers and is a promising material for applications involving adsorption of gases such as CO. In this work, the solvothermal synthesis and detailed characterization of the gallium- and indium-fumarate MOFs (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 73 publications
(211 reference statements)
1
33
0
Order By: Relevance
“…In recent years, we have examined CO 2 dynamics in three types of MOFs where the CO 2 molecules are adsorbed at the framework hydrogen atoms: (i) MIL-53 (M), M = Al, Ga; 66 (ii) α-Mg 3 (HCOO) 6 ; 39 and (iii) Al-fumarate. 67 In (i) and (iii), the CO 2 molecules are adsorbed at the hydrogens of the bridging hydroxyl groups, whereas in (ii) the CO 2 molecules are adsorbed at the hydrogens of the formate linkers. The common motion experienced by CO 2 in these types of MOFs is the local rotation or wobbling motion.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, we have examined CO 2 dynamics in three types of MOFs where the CO 2 molecules are adsorbed at the framework hydrogen atoms: (i) MIL-53 (M), M = Al, Ga; 66 (ii) α-Mg 3 (HCOO) 6 ; 39 and (iii) Al-fumarate. 67 In (i) and (iii), the CO 2 molecules are adsorbed at the hydrogens of the bridging hydroxyl groups, whereas in (ii) the CO 2 molecules are adsorbed at the hydrogens of the formate linkers. The common motion experienced by CO 2 in these types of MOFs is the local rotation or wobbling motion.…”
Section: Resultsmentioning
confidence: 99%
“…The motion of CO 2 and the interactions with framework in various MOFs were comprehensively studied by VT 13 C static NMR experiments. [81] Diamine-appended MOFs are highly efficient for CO 2 adsorption from various gas mixtures. [82] Recently, multinuclear SSNMR spectroscopy has been utilized to characterize CO 2 chemisorption in diamine-appended metal-organic frameworks.…”
Section: Co 2 In Mofsmentioning
confidence: 99%
“…This may, in part, explain why most of the studies found in the literature of Ga 3+ -CP/MOFs report only their structures. Furthermore, most of the applications that have been studied are related to those that are also found for Al 3+ -CP/MOFs (Banerjee et al, 2011;Zhang et al, 2018;Reinsch & De Vos, 2014;Canivet et al, 2014;Zhou et al, 2012). For certain applications, Ga 3+ -CP/ MOFs excel, even surpassing the performance of the Al 3+ -CP/ MOFs (Coudert et al, 2014;Ramaswamy et al, 2017;Weber et al, 2016;Gao et al, 2014).…”
Section: Chemical Contextmentioning
confidence: 99%